Use of Islamic Malay Texts in Language Learning for Character Building - Ahmad Laut Hasibuan; Saiful Anwar Matondang; Surya Aymanda Nababan (JETL (Journal of Education, Teaching and Learning), 2022)
The formation of student character requires relevant teaching materials. One of the efforts to provide appropriate teaching materials is to explore the content of ancient manuscripts. Through the Research and Development (R & D) method from old manuscripts to help make the high school curriculum. It is hoped that the application of learning models that are sourced from old texts will be designed to be more attractive and of high quality so that students are more interested in taking language education lessons. The final goal that is expected is that the results of language education learning can shape the character of the nation and fortify our young generation from disgraceful acts so that during their leadership, disgraceful acts are increasingly unheard. To achieve this goal, it is necessary to revitalize ancient manuscripts as language-learning materials in Sumatra. To shape human character, teaching materials from classical Malay ancient manuscripts are needed. The results showed that using the old text as a language learning material can shape the character of students.